Covalently-assembled single-chain protein nanostructures with ultra-high stability - Wenqin Bai (Nature Portfolio, 2019)
De novo protein nanostructures are typically assembled via top-down approaches. Here, the authors developed a bottom-up approach, using split inteins to ligate multiple copies of a three-helix bundle to create 2D triangular and square-shaped structures with high stability.